Laser-Casein phosphopeptide effect on remineralization of early enamel lesions in primary teeth - Asl-Aminabadi, N; Najafpour, E; Samiei, M; Erfanparast, L; Anoush, S; Jamali, Z; Pournaghi-Azar, F; Ghertasi-Oskouei, S (Journal of clinical and experimental dentistry, 2015)
The aim of this study was to assess the effect of Nd:YAG laser irradiation following casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) application on calcium and phosphate concentration and surface microhardness (SMH) of enamel surface in artificial white spot lesions of primary teeth. Eighty teeth with artificial white spot lesions were randomly divided into four groups: (A) distilled and deionized water, (B) Nd:YAG laser, (C) CPP-ACP crème, & (D) CPP-ACP plus laser. SMH was measured using Vickers diamond indenter in Vickers Hardness Number (VHN). Two samples of each group were analyzed using scanning electron microscope (SEM). The results were analyzed with the SPSS 17/win. The subjects of group D demonstrated a significant increase in the calcium and phosphate contents of enamel surface compared to those of groups A (P < 0.001, P < 0.001), B (P < 0.001, P < 0.001) and C (P = 0.024, P = 0.04), respectively. A statistically significant difference was seen for mean VHN between groups A and B (P = 0.002). SEM evaluations confirmed the results. The combination of Nd:YAG laser and CPP-ACP crème could be recommended as an effective preventive modality for remineralizing of white spot lesions in primary teeth. Key words:CPP-ACP, enamel remineralization, microhardness, Nd:YAG, primary teeth, SEM.